Synthesis of biomass-derived carbon quantum dots/polyaniline nanocomposite for photocatalytic degradation of brilliant green dye and bioimaging applications - Qurtulen Qurtulen; Mohammad Mujahid; Omar A Al-Hartomy; Ahmed Obaid M Alzahrani; Asrar Ahmad (Nano Express)
Currently, highly efficient nano photocatalysts driven by visible light are being developed for organic pollutant removal and bioimaging applications. Carbon quantum dots (CQDs) have been shown to enhance the photocatalytic activity of nanocomposites. In this work, we report the surface modification of a polyaniline (PANI) photocatalyst using hydrothermally produced CQDs. The synthesized nanocomposite (CQDs/PANI) was characterized using advanced analytical techniques. These studies confirmed the presence of PANI and CQDs and demonstrated their roles in improving electron-hole pair separation and reducing the band gap of PANI. The photocatalytic activity of the CQDs/PANI (5 wt%) nanocomposite was evaluated under visible light irradiation for the degradation of Brilliant Green dye in aqueous solution. The synthesized photocatalyst achieved nearly 100% dye removal after 35 min of irradiation. The kinetics of the dye degradation was predicted using the Langmuir–Hinshelwood model, with a rate constant (k _app ) of 0.0351. The study also investigated the effects of initial dye concentration, pH, and photocatalyst dosage on the photocatalytic activity of CQDs/PANI (5 wt%). The optimal conditions were 15 mg of photocatalyst per 50 ml of a 10-ppm dye solution, with a neutral pH of 7. The photocatalyst demonstrated excellent stability and reusability over four reaction cycles. The exact cell line of human breast cells used in this work is MCF-7. Additionally, the nanocomposite was evaluated for cell imaging in human breast cancer cells (MFC-7), showing excellent biocompatibility and low cytotoxicity.